(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Lugovskaya E. The formation of the special competence of technicians, engineers hazyaystva agriculture in the study of special subjects. In this article the term "professional discipline", "professional competence" mechanical engineering agriculture refined professional specialty discipline "Maintenance and repair of machinery and equipment agricultural production" and their functions.